PRAWO BOLSZEWIKÓW: REWOLUCJA I EWOLUCJA - Lityński, Adam (Zeszyty Prawnicze, 2016)
The Bolsheviks’ Law: Revolution and Evolution Summary The Bolsheviks presented revolutionary ideas and concepts about creating revolutionary law. This law was supposed to be totally different from the “bourgeois” one. The revolutionary law was supposed to exist only during the transition period, on the way to Communism. According to concepts of Marx and Lenin, the state and law in Communism should disappear completely. However, in the mid 30’s revolutionary concepts and revolutionary law became more civilized and they started to approach to the European regulations. We can conclude the paradox of history – that the gradual change and process of making Soviet law more civilized started when the Stalin’s terror was the most cruel. The reality and the legal norm were completely divergent at that time.